2016
DOI: 10.1111/phn.12302
|View full text |Cite
|
Sign up to set email alerts
|

Retail Food Store Access in Rural Appalachia: A Mixed Methods Study

Abstract: Findings from this study can help public health nurses engage with communities to make affordable, healthy foods more accessible. Recommendations are made for educating low-income consumers and partnering with food stores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(30 reference statements)
1
8
1
Order By: Relevance
“…Scoring was informed by past work [27] to include more food items, such as yogurt and cheese in the dairy category that assist in mitigating lead absorption in the body. Shaver et al [27] also informed the inclusion and scoring criteria for frozen fruits and vegetables based on Cavanaugh et al [25] and the NEMS-S-Revised by the Rudd Center [34] NEMS for Corner Stores (NEMS-CS), as well as expanded protein food items. The application of scoring was based on the original criteria developed by Glanz et al [11] expanded fruit and vegetable criteria from Franco et al [23] frozen fruits and vegetables from Cavanaugh et al [25] and the additional dairy, protein, and beans items adapted by Shaver et al [27].…”
Section: Availability Index Developmentmentioning
confidence: 99%
“…Scoring was informed by past work [27] to include more food items, such as yogurt and cheese in the dairy category that assist in mitigating lead absorption in the body. Shaver et al [27] also informed the inclusion and scoring criteria for frozen fruits and vegetables based on Cavanaugh et al [25] and the NEMS-S-Revised by the Rudd Center [34] NEMS for Corner Stores (NEMS-CS), as well as expanded protein food items. The application of scoring was based on the original criteria developed by Glanz et al [11] expanded fruit and vegetable criteria from Franco et al [23] frozen fruits and vegetables from Cavanaugh et al [25] and the additional dairy, protein, and beans items adapted by Shaver et al [27].…”
Section: Availability Index Developmentmentioning
confidence: 99%
“…Point exposure may be more sensitive to neighborhood definition even in rural areas. Also, given research showing how far some rural residents have to travel to access amenities like grocery stores (Thatcher et al, 2017) and for health care (Yaemsiri et al, 2019), buffer sizes many need to be even larger to even have any exposure at all. This may also suggest why there is no significant difference in deprivation across neighborhood definitions in rural settings.…”
Section: Articlementioning
confidence: 99%
“…A study in a rural Appalachian county reported similar results, with supermarkets having the biggest variety of healthy foods while convenience stores had reduced availability and higher prices for the healthy food items assessed using the NEMS-S (Thatcher et al, 2017). Studies highlight that regardless of geography of residence; supermarkets tend to provide healthier options more often and larger varieties of healthy items then smaller store types.…”
Section: Review Of the Literaturementioning
confidence: 85%
“…A limitation of the quantitative studies to date is that they have occurred in only two geographic regions: Texas (Sharkey & Horel, 2008) and South Carolina (Liese et al, 2007). Rural studies have also found that among stores available in rural areas, supermarkets offer the greatest varieties of the healthy food items assessed, with convenience stores offering the fewest healthy items (Liese et al, 2007;Thatcher, Johnson, Zenk, & Kulbok, 2017).…”
Section: Geography Of Residence and The Food Environment Living In Amentioning
confidence: 99%